The Relationship between Time Management and Academic Procrastination in Nursing Students (S1) at STIKes Medistra Indonesia 2022 - Ibnu Rosyid, Afif; Kiki Deniati; Lisna Agustina (Rena Cipta Mandiri, 2022)
Academic procrastination is a behavior to procrastinate in starting work or completing academic assignments given by lecturers. Academic procrastination is influenced by several factors including time management, academic confidence/ability, attention disorders, social factors, personal initiative, and laziness. Time management is the ability to manage time effectively and efficiently when carrying out an activity that leads to a specific goal. This study aims to determine whether there is a relationship between time management and academic procrastination in students of the Nursing Science Study Program (S1) at STIKes Medistra Indonesia in 2022. This research method uses a correlational research design with a cross sectional approach. The population in this study were regular active students of the Nursing Science Study Program (S1) at STIKes Medistra Indonesia from level I, level II, and level III totaling 197 students. After entering into the Slovin formula, the number of samples in this study was 132 students using the Probability Sampling method with the type of Simple Random Sampling. From the results of the Chi-Square statistical test obtained p value of 0.000, it can be concluded that p value (0.000) < value (0.05), this indicates that there is a relationship between time management and academic procrastination in nursing students (S1 ) at STIKes Medistra Indonesia. Time management can affect academic procrastination. So the better time management owned by students, the lower academic procrastination carried out by students and vice versa